Digital Transformation and Tax Policy: Analyzing MSME Resilience in Post-Pandemic Era Through E-Commerce Adoption and Tax Incentive Utilization in Bandar Lampung Central Market - Maulifah, Elia; Hanif, Hanif; Kurniawan, Agus; Audia, Nanda (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study investigates the intersection of digital transformation and fiscal policy in supporting Micro, Small, and Medium Enterprise (MSME) resilience in the post-COVID-19 landscape. Through comprehensive interviews with 100 MSME owners in Bandar Lampung's Central Market, we examine the effectiveness of government tax incentives and digital platform adoption as key survival strategies. Our findings reveal a significant gap in tax incentive utilization, with 61% of MSMEs not accessing these benefits primarily due to insufficient socialization and complex regulatory frameworks. However, MSMEs demonstrate remarkable adaptability in digital transformation, with 50% adopting Shopee and 29% utilizing Tokopedia as primary e-commerce platforms. The study identifies a clear pattern of digital platform preference, with businesses leveraging various online marketplaces to expand market reach and enhance competitiveness. The research also examines these adaptations through an Islamic economic perspective, evaluating the alignment of digital commerce and tax incentive utilization with Islamic business principles. Our findings suggest that while tax incentive programs have shown limited effectiveness, digital platform adoption has emerged as a crucial factor in business sustainability. This research contributes to understanding the evolving dynamics of MSME resilience in the digital age. It provides practical insights for policy enhancement and business strategy development in the post-pandemic era.